这道题不用那么复杂。
先移项。
(x-4)/(x-5)-(x-5)/(x-6)=(x-7)/(x-8)-(x-8)/( x-9)
再通分。
(x-4)(x-6)/(x-5)(x-6)-(x-5)(x-5)/(x-5)(x-6)=(x-7)(x-9)/(x-8)(x-9)-(x-8)(x-8)/(x-8)(x-9)
再化简。
(xˇ2-10x+24-xˇ2+10x-25)/(x-5)(x-6)=(xˇ2-16x+63-xˇ2+16x-64)/(x-8)(x-9)
得:-1/(xˇ2-11x+30)=-1/(xˇ2-17x+72)
交叉相乘。
xˇ2-11x+30=xˇ2-17x+72
然后6x=42 。
最后求得:x=7。
左右两边同乘以(X-5)(X-6)(X-8)(X-9)
得到(X-4)(X-6)(X-8)(X-9)-(X-5)(X-5)(X-8)(X-9)=(X-5)(X-6)(X-7)(X-9)-(X-5)(X-6)(X-8)(X-8)
整理得到-(X-8)(X-9)=-(X-5)(X-6)
展开解得X=7
x-4)/(x-5) = 1- 1/(x-5)
因此, 2-(1/(x-5) +1/(x-9)) =2+ 1/(x-8) +1/(x-6)
即:0= 1/(x-8) +1/(x-6)+1/(x-5) +1/(x-9)
可以看出 X 在 5-9中间
这回就猜吧?
其实 X-5 = 9-x
X=7